Briavioids A–C, discovery of new polyacetoxybriaranes from octocoral Briareum violaceum (Quoy & Gaimard, 1833). (22nd October 2022) - Huynh, Thanh Hao; Wen, Zhi-Hong; Chien, Su-Ying; Chung, Hsu-Ming; Su, Jui-Hsin; Fang, Lee-Shing; Wu, Yu-Jen; Lin, Shih-Hsiung; Sung, Ping-Jyun
Abstract: Three new polyacetoxybriarane diterpenoids, briavioids A–C (1 –3 ), as well as two known analogues, briaexcavatin M (4 ) and excavatolide F (5 ), were isolated from a cultured soft coral Briareum violaceum . The structures and relative stereochemistry of new metabolites 1 –3 were assigned on the basis of NMR studies. Single-crystal X-ray diffraction analysis was performed to identify the structure of 1 . Briaranes 1 –5 were assessed in terms of their inflammation activity by screening their inhibition abilities against iNOS protein in LPS-stimulated RAW264.7 macrophage cells. Graphical abstract: Image 1 Highlights: Three previously-undescribed briaranes, briavioids A–C (1 –3 ), were isolated from a cultured octocoral Briareum violaceum. The structure of briavioid A was confirmed by a single-crystal X-ray diffraction analysis. Excavatolide F reduced the release of iNOS.